Familial Idiopathic Intracranial Hypertension in Two Non-obese Chinese Sisters - Qiao, Lei; Wei, Yanping (Frontiers in Neurology, 2020)
Objective: Familial idiopathic intracranial hypertension (FIIH) was rare. The etiology of FIIH was not clear. Methods: We report two nonobese Chinese sisters who met the criteria of FIIH. Meanwhile all the literature of familial IIH (FIIH) were reviewed and analyzed. Results: These two sisters presented with headache and visual impairment at mid-thirties. No comorbidities and defined causes were detected. Based on the literature review, we got the following information: 1. The incidence of FIIH was significantly higher in women than in men. 2. Childbearing age and obesity predisposed females to FIIH, while they were uncommon in male patients of FIIH. 3. Affective disorders, especially depression, and asthma were the two most common comorbidities in FIIH patients. 4. Parent-child relationship was the most common, especially mother-daughter relation, followed by siblings. Conclusion: Especially when the patients presented with headache, and empty sella were found on MRI, or visual impairment with or without papilla edema, intracranial hypertension should be excluded.